How actors move from primary agency to institutional agency: A conceptual framework and empirical application. (July 2021) - Maier, Florentine; Simsa, Ruth
This article contributes to the understanding of actors and agency in the theorization of institutional work. We analyse institutional work as a specific kind of social action that involves exercising institutional agency (with an articulate awareness of institutions) as opposed to primary agency (taking institutions for granted). We propose a conceptual framework for combining a view of actors, who have agency and may engage in institutional work, with a view of actors as socially constructed, in line with critical-realist ontology. Applying this framework to the empirical case of the Spanish social movement 15M, we examine how actors moved from having primary agency to having institutional agency and how organization mattered for this process. We find that organizing by experienced organizers, the founding of new organizations and prefigurative organization were of crucial importance for the increase in institutional agency.